POTENSI PENGEMBANGAN WISATA ALAM DI HABITAT MALEO (Macrocephalon maleo) TAMAN NASIONAL LORE LINDU BIDANG PENGELOLAAN WILAYAH (BPW) I SALUKI KEC. GUMBASA KAB. SIGI - Nurdianti, Asma; Ningsih, Sri; Sustri, Sustri (Warta Rimba, 2013)
The aims of this study were to know the potency and the development of natural tourism objects in Saluki Village, Gumbasa Distric, Sigi Regency, Central Sulawesi. The respondents were selectedby using purposive sampling methods. The study was employedStrengths-Weaknesses-Opportunities-Threats (SWOT) analysis. The results showed that the potency of natural tourisms around Maleo (Macrocephalon maleo) habitat were Maleo birds, camping ground, river, Hot water, waterfall, tracking and hiking area, and other objects for science and research development. Hence, the development form of natural tourism in this area was divided in two parts. First, an area used as nesting grounds and activities of Maleo birds. Second, an area purposed for modern tourism activities and divided four zones (A, B, C dan D). Keywords: Potency, Development, Natural Tourisms, Maleo (Macrocephalon maleo),